2020
DOI: 10.1186/s12935-020-01538-8
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of lncRNA UCA1 enhances radiosensitivity in prostate cancer by suppressing EIF4G1 expression via sponging miR-331-3p

Abstract: Background We aimed to explore the role of long noncoding RNA urothelial carcinoma-associated 1 (lncRNA UCA1) and its underlying mechanism in the radioresistance of prostate cancer (PCa). Methods QRT-PCR was conducted to measure the expression of UCA1, microRNA-331-3p (miR-331-3p) and eukaryotic translation initiation factor 4 gamma 1 (EIF4G1) in PCa tissues and cells. The relative protein level was determined by western blot assay. Cell proliferation and apoptosis were detected by MTT, colony formation assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In prostate cancer, lncRNA UCA1 levels were found to be positively correlated with eIF4G1 levels. UCA1 enhances eIF4G1 levels via sponging miR-331-3p, while knockingdown of UCA1 sensitizes prostate cancer cells to radiotherapy by suppressing eIF4G1 expression via miR-331-3p/eIF4G1 axis [ 150 ]. In another study, lncRNA GAPLINC increased the eEF2K expression by serving as a sponge for miR-661, thereby promoted proliferation and progression of non-small cell lung cancer [ 64 ].…”
Section: Acting Mechanisms Of Lncrnas In the Regulation Of Translamentioning
confidence: 99%
“…In prostate cancer, lncRNA UCA1 levels were found to be positively correlated with eIF4G1 levels. UCA1 enhances eIF4G1 levels via sponging miR-331-3p, while knockingdown of UCA1 sensitizes prostate cancer cells to radiotherapy by suppressing eIF4G1 expression via miR-331-3p/eIF4G1 axis [ 150 ]. In another study, lncRNA GAPLINC increased the eEF2K expression by serving as a sponge for miR-661, thereby promoted proliferation and progression of non-small cell lung cancer [ 64 ].…”
Section: Acting Mechanisms Of Lncrnas In the Regulation Of Translamentioning
confidence: 99%
“…For example, Ting et al ( 29 ) systematically analyzed a large number of studies and found that miR-155, miR-334, miR-21, miR-146b-5p and miR-17/92 clusters have certain value in predicting the chemotherapy response in DLBCL. In previous research, UCA1 was revealed to competitively bind with several miRNAs ( 13 , 30 ). Gao et al ( 31 ) confirmed that UCA1 facilitated thyroid cancer cell ability and metastasis by decreasing the expression of miR-497-3p.…”
Section: Discussionmentioning
confidence: 95%
“…Urothelial carcinoma-associated 1 (UCA1) was first identified in bladder transitional cell carcinoma, and the entire sequence consisted of three exons with a length of 1.4 kb ( 12 ). Scientists have revealed that UCA1 is dysregulated in several human cancers and plays an important role in cancer progression ( 13 ). In 2006, upregulation of UCA1 was revealed in bladder cancer, and enhanced cell growth and invasion viability ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…CAMK2N1, characterized as an inhibitor of CaMKII (calcium/calmodulin-dependent protein kinase II) [32][33][34][35], has been identi ed as a downstream transcriptional target of PRMT5 in PCa cells. PRMT5-mediated H4R3me2s and H3R8me2s modi cations were signi cantly enriched at the promoter regions and at the vicinity of the transcription start site of CAMK2N1 gene in PCa cells, especially at the core region of CAMK2N1 promoter.…”
Section: Discussionmentioning
confidence: 99%